Landscape simplification increases vineyard pest outbreaks and insecticide use. (13th October 2020) - Paredes, Daniel; Rosenheim, Jay A.; Chaplin‐Kramer, Rebecca; Winter, Silvia; Karp, Daniel S.
Abstract: Diversifying agricultural landscapes may mitigate biodiversity declines and improve pest management. Yet landscapes are rarely managed to suppress pests, in part because researchers seldom measure key variables related to pest outbreaks and insecticides that drive management decisions. We used a 13‐year government database to analyse landscape effects on European grapevine moth ( Lobesia botrana ) outbreaks and insecticides across c . 400 Spanish vineyards. At harvest, we found pest outbreaks increased four‐fold in simplified, vineyard‐dominated landscapes compared to complex landscapes in which vineyards are surrounded by semi‐natural habitats. Similarly, insecticide applications doubled in vineyard‐dominated landscapes but declined in vineyards surrounded by shrubland. Importantly, pest population stochasticity would have masked these large effects if numbers of study sites and years were reduced to typical levels in landscape pest‐control studies. Our results suggest increasing landscape complexity may mitigate pest populations and insecticide applications. Habitat conservation represents an economically and environmentally sound approach for achieving sustainable grape production. Abstract : Diversifying agricultural landscapes may mitigate biodiversity declines and improve pest management. We used a 13‐year government database to analyse landscape effects on European grapevine moth (Lobesia botrana) outbreaks and insecticides across c . 400 Spanish vineyards. Our results suggest increasing landscape complexity may mitigate pest outbreaks and insecticide applications.